The Effect of Halal Certification, Product Quality, and Price on Purchase Intention toward Kutaradja Fried Chicken - Meylin Alfionita; Ahmad Nizam; Junia Farma; Khairil Umuri (Universitas Syiah Kuala, 2026)
This study aims to examine the influence of halal certification, product quality, and price on students’ purchase intention towards Kutaradja Fried Chicken at the Faculty of Economics and Business, Syiah Kuala University. A quantitative approach was employed using primary data collected from 100 respondents through questionnaires, selected via purposive sampling. The data were analyzed using multiple linear regression with SPSS. The findings reveal that product quality and price have a positive and significant effect on purchase intention, while halal certification has a negative and significant effect. This suggests that halal certification is perceived as a basic requirement rather than a differentiating factor among students, whereas product quality and price play a more dominant role in shaping purchasing decisions. Simultaneously, all independent variables significantly influence purchase intention. The findings imply that business practitioners should prioritize improving product quality and maintaining competitive pricing strategies, while consistently ensuring halal compliance to sustain consumer trust. Theoretically, this study contributes to consumer behavior literature by highlighting the shifting role of halal certification from a competitive advantage to a hygiene factor in a highly religious context. Practically, it offers insights for local fast-food businesses in designing value-based marketing strategies targeting student consumers. However, this study is limited to a specific sample of students within one faculty and focuses only on three variables, which may not fully capture broader consumer behavior. Future research is recommended to incorporate additional variables and broader populations to enhance generalizability.